I HAVE CHOSEN YOU AMONG THE OTHERS!: THE IMPACT OF LEADER-MEMBER EXCHANGE, PERCEIVED SUPERVISOR SUPPORT AND ORGRANIZATIONAL CITIZENSHIP BEHAVIOR IN ENHANCING SUBORDINATES’ PERFORMANCE IN HOSPITALITY INDUSTRY - Adityaji, Rizki; Kartika, Endo Wijaya; Oktavio, Adrie (FEB Universitas Sam Ratulangi Manado, 2021)
Abstract: Covid-19 pandemic, which has occured for more than a year has had a bad impact on companies in Indonesia. This kind of condition urges superiors from the hospitality industry to immediately take some strategic steps to save their companies in order to survive. In such a situation, superiors are forced to select subordinates who should be retained or have to be released to reduce companies’ burden. For subordinates who are still retained by their superiors, it is due to good judgment from the superior so that these subordinates are still considered worthy enough of being retained and it is also hoped that the superior’s decision is correct by ensuring that these subordinates could show better working results. This study is conducted to add an empirical contribution to examine the role of LMX on PSS and OCB in improving subordinates’ performance, specifically in Indonesian context during Covid-19 pandemic. The data is collected from 264 respondents who work in the hospitality industry in East Java and Bali provinces, Indonesia. The results show that LMX has a positive and significant effect on OCB; LMX has a positive and significant effect on PSS; and PSS has a positive and significant effect on OCB; and finally OCB has a positive and significant effect on subordinates’ performance.Keywords: Leader-Member Exchange; Perceived Supervisor Support; Organizational Citizenship Behavior; Subordinates’ Performance; Hospitality Industry Abstrak: Pandemi Covid-19 yang terjadi lebih dari setahun membawa dampak buruk bagi perusahaan-perusahaan di Indonesia. Kondisi semacam ini mendesak para pimpinan dari industri perhotelan untuk segera mengambil beberapa langkah strategis untuk menyelamatkan perusahaannya agar tetap bertahan. Dalam situasi seperti itu, atasan terpaksa memilih bawahan yang harus dipertahankan atau harus dilepaskan untuk mengurangi beban perusahaan. Bagi bawahan yang masih dipertahankan oleh atasannya, hal ini dilatarbelakangi oleh penilaian yang baik dari atasan sehingga bawahan tersebut masih dianggap cukup layak untuk dipertahankan dan juga diharapkan keputusan atasan tersebut tepat dengan memastikan bahwa bawahan tersebut dapat menunjukkan kinerja yang lebih baik. Penelitian ini dilakukan untuk menambah kontribusi empiris untuk mengkaji peran pertukaran pemimpin-anggota pada perilaku kewarganegaran organisasi dalam meningkatkan kinerja bawahan, khususnya dalam konteks Indonesia di masa pandemi Covid-19. Data dikumpulkan dari 264 responden yang bekerja di industri perhotelan di provinsi Jawa Timur dan Bali, Indonesia. Hasil penelitian menunjukkan bahwa pertukaran pemimpin-anggota berpengaruh positif dan signifikan terhadap perilaku kewarganegaran organisasi; serta perilaku kewarganegaran organisasi juga berpengaruh positif dan signifikan terhadap kinerja bawahan.Kata kunci: Leader-member Exchange; Perceived Supervisor Support; Organizational Citizenship Behavior; Kinerja Bawahan; Industri Perhotelan